El muro (2020)
I believe we live in a society that is constantly evolving and transforming, and that these changes have connotations in different areas. The accelerated and constant movement of the dynamics that surround us is immeasurable and architecture and design cannot be kept out of these transformations. For this reason I believe that architecture and design are not something finished, they are a process. If they do not mutate and do not evolve in relation to the environment to which they belong, they are condemned to disappear or to belong to oblivion and abandonment. In this sense, and after studying the conditions of the place to work, a great concern arises around the wall. The wall is a fundamental architectural element, perimeter, present, and marked in the sector to work. A wall that I do not currently conceive as architecture given the connotations that its presence has derived in the surrounding environment...